Method for preparing high aspect ratio anti-reflection structure based on laser V-shaped scanning
The laser "V" type scanning method is used to prepare a high aspect ratio micro-nano cone-tip composite structure on the surface of metal and partially hard and brittle non-metallic materials, which solves the problem that the prior art is difficult to achieve high absorption rate in the ultra-wide spectrum range and achieves an ultra-high light absorption effect.
Patent Information
- Application Number
- CN202411597265.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-11
AI Technical Summary
It is difficult to prepare high aspect ratio anti-reflective structures on metal and partially hard and brittle non-metallic materials surfaces, especially to achieve ultra-low reflectivity and ultra-high absorption in the ultra-wide spectrum.
A laser "V" type scanning method is used to prepare a high-deep aspect ratio micro-nano cone-tip composite structure, absorb electromagnetic waves through a geometric light capture mechanism, and the generated oxide layer and nanoparticle layer are used to enhance the light absorption effect.
It achieves a high absorption rate of more than 98% in the range of 200nm–25μm, and reaches an emissivity of more than 99% in the 400-700nm band, and has high-efficiency light absorption capability with ultra-wide spectrum.
Smart Images

Figure CN119566518A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of laser micro-nano processing, and proposes a universal "V"-shaped scanning method for preparing an anti-reflection structure with a high aspect ratio on the surface of metals and some hard and brittle non-metallic materials, so as to achieve ultra-low reflectivity and ultra-high absorption rate within an ultra-wide spectrum (200nm-25μm) on the surface of various materials. Background Art
[0002] In recent years, achieving functional metal surfaces with minimal optical reflection over an ultra-wideband spectrum has attracted widespread research interest among researchers. A large amount of research work has focused on developing surfaces with high electromagnetic absorption or emission in the ultraviolet, visible and infrared regions, which play a vital role in blackbody radiation calibration, spacecraft thermal management and other fields. However, the inherent large optical impedance mismatch between metal and free space has created a huge obstacle to achieving this goal.
[0003] The current mainstream surface treatment methods with high emissivity can be simply divided into two categories:
[0004] 1. High emissivity coating and paint method: The coating and paint method refers to applying a high emissivity coating or paint on the substrate, and using the high absorptivity of the coating and paint to achieve high absorption of the substrate. This method has many advantages, including simple use and wide applicability; but it also has inevitable disadvantages, that is, the absorption spectrum is usually narrow-band absorption, and the coating may be troubled by environmental pollution, and stability is a big problem, and it is very easy to lose its effect in harsh environments such as space;
[0005] 2. Surface microstructure method; Surface microstructure method includes metamaterial method with precise definition of surface micro-nanostructure and laser micro-nano processing for preparing micro-nano composite structure surface. Metamaterial method uses alternating metal dielectric layers and metamaterials with different surface shapes. Theoretical work has proved adjustable and near-perfect wide-angle absorption in various wavelength ranges of infrared spectrum, but the complexity, expensiveness and stability of these structure preparation methods such as photolithography are still a big problem. Laser processing surface can obtain cross-scale, multi-level micro-nano composite structure, which has good anti-reflection effect in part of wide spectrum range. The microstructures used are micropores, micro-cones and other microstructures. However, the aspect ratio of micro-cones and other structures prepared by laser is limited, and the anti-reflection effect is mainly concentrated in the ultraviolet and visible regions, and it is impossible to achieve ultra-high anti-reflection effect in the ultra-wide spectrum range across ultraviolet-visible-near infrared-mid-infrared. Summary of the invention
[0006] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide a method for preparing a high aspect ratio anti-reflection structure based on laser "V" scanning, and the preparation method can prepare a micro-nano cone tip composite structure with a high aspect ratio on the surface of various metals and some hard and brittle non-metallic materials. The micron-scale cone tip structure can absorb the incident electromagnetic wave by geometric light capture. The larger the aspect ratio of the cone tip structure, the better the geometric light capture effect. The traditional laser cross-type scanning method cannot well adjust the period and aspect ratio of the micron cone tip structure. For a specific processing system, only when the laser focus spot matches the period of the cross-type scanning can the cone tip structure under a specific period be processed. If the period is large, there will be a square unablated area on the top of the processed micro-nano composite structure, which directly affects the structure's absorption of the incident electromagnetic wave. Therefore, the present invention proposes that laser "V" scanning can better adjust the period and depth of the cone tip structure, and can prepare a cone tip structure with a high aspect ratio, which has a very good geometric light trapping effect. The oxide layer and nanoparticle layer generated during the processing can act as an effective medium to further increase the light absorption effect. In summary, the present invention can prepare high aspect ratio micro-nano cone-tip composite structures on the surfaces of various metal materials and some hard and brittle non-metallic materials through the laser "V" scanning method, and has ultra-high light absorption effect in an ultra-wide spectrum (200nm-25μm).
[0007] The present invention is achieved through the following technical solutions:
[0008] A method for preparing a high aspect ratio anti-reflection structure based on laser "V" scanning, specifically comprising the following steps:
[0009] Step 1: Processing of samples to be processed;
[0010] The metal sample to be processed is placed in a sealed polytetrafluoroethylene beaker with acetone solution, taken out after ultrasonic cleaning, rinsed with ethanol and deionized water in turn, and placed in a low-temperature oven for drying; then the metal sample is taken out for use, and the sample preparation is completed;
[0011] Step 2: Processing metal samples with femtosecond laser in atmospheric environment;
[0012] First, the sample is fixed on a two-dimensional mobile platform, which is composed of two one-dimensional mobile translation stages to meet the precise movement of the sample in the XY plane. The femtosecond laser emitted by the femtosecond laser amplifier enters the three-dimensional galvanometer processing system focused by the field lens after beam expansion. The galvanometer of the three-dimensional galvanometer processing system is installed on a z-axis translation stage that can move up and down. The femtosecond laser deflected by the galvanometer is then focused on the upper surface of the sample by the field lens. Then, the pre-designed processing file is read into the processing program, and the "V" scanning method is used for direct writing processing. Finally, the multi-level micro-nano composite structure is prepared on the sample surface by the "V" scanning method of the three-dimensional galvanometer processing system focused by the field lens.
[0013] Step 3: ultrasonic treatment of metal samples;
[0014] The sample obtained in step 2 is placed in deionized water for ultrasonic cleaning to clean the debris remaining after processing, leaving only the stable micron cone tip structure and nanoparticle structure, and then dried in a dryer or blown dry with an ear bulb. At this point, the preparation of a metal sample with high emissivity is completed.
[0015] Furthermore, the material of the metal sample to be processed described in step 1 is not limited to a single metal, but should include various metals and some hard and brittle non-metals, such as copper, aluminum alloy, stainless steel, titanium alloy and other metals and silicon carbide, diamond, silicon and other non-metals; the size of the metal sample is 3cm-10cm, the thickness is 1mm-10mm, the polytetrafluoroethylene beaker is sealed in the fume hood for ultrasound to prevent the acetone solution from volatilizing, the ultrasound time is 0.1h-2h, and the low-temperature oven temperature is set to 50℃-100℃.
[0016] Furthermore, the x-axis and y-axis movement ranges of the two-dimensional moving platform in step 2 are 0-10cm, the movement range of the z-axis translation stage is 0-10cm, and the accuracy is 1μm; the galvanometer used in the three-dimensional galvanometer processing system is composed of an XY optical scanning head, an electronic drive amplifier and an optical reflective lens. The signal provided by the computer controller is sent to the electronic drive amplifier, and the electronic drive amplifier is used to drive the XY optical scanning head, thereby controlling the high-speed deflection of the laser beam in the XY plane, and the movement accuracy is 10-100nm; the laser polarized by the galvanometer is then focused on the sample surface through the field lens to realize femtosecond laser direct writing processing.
[0017] Furthermore, the fundamental wavelength of the femtosecond laser in step 2 is 1030nm, and the wavelength becomes 515nm after double frequency, which is a femtosecond laser in the visible region, or a near-ultraviolet femtosecond laser of 343nm is obtained after triple frequency; the use of nanosecond laser or picosecond laser can also use "V" type scanning to quickly complete the preparation of cone-shaped micro-nano composite structures; the repetition frequency of the laser is 50kHz-1000kHz, and the pulse width is 280fs; the focal length of the focusing field lens used is 5-20cm, which meets the requirements of large-area processing, and even by using an objective lens or lens focusing, the required cone-shaped micro-nano composite structure can still be quickly prepared by "V" type scanning; the single pulse energy of laser ablation is 1-100μJ, and the laser scanning speed is 1-1000mm / s, which meets the requirements of high-speed processing; the point spacing of the processing data is 50-10000nm, the period is 10-100μm, the width of the surface scanning is 10-100μm, and the layer spacing is 1-30μm.
[0018] Furthermore, in step 2, a "V" type scanning method is used for direct writing processing, which specifically includes the following contents:
[0019] First, a surface scan with a certain width is performed from left to right and then from right to left on the x-axis, wherein the certain width is less than one cycle; then, a surface scan is performed after one cycle, and the scanning is repeated in this way, wherein the number of back-and-forth surface scans on the x-axis is equal to the total width of the sample to be processed divided by the cycle in the y-direction; similarly, after the x-axis scan is completed, the y-axis scan is performed back and forth, thereby realizing the surface scan at the same z-axis position; next, a second scan is performed, the z-axis position is lowered, so that the laser focus further penetrates into the structure, the width of the surface scan is reduced, and the cyclic surface scans of the x-axis and y-axis are repeated; the z-axis is continued to be lowered to perform a surface scan with a reduced width, and the cycle is repeated until the surface scan width is reduced to 0, thereby realizing the processing of the set high aspect ratio structure;
[0020] Among them, the total number of scans is 1-100 times. Each time a layer is scanned, the z-axis is reduced by one layer spacing, and the width of the surface scan is also reduced by a set width; the width reduced by each surface scan and the initial width of the surface scan determine the total number of scans, and the scanning stops after the width of the surface scan is reduced to 0. In this way, a uniform cone-shaped micro-nano composite structure with a larger aspect ratio can be obtained. Different structural morphologies have a great influence on the final emissivity test results. Of course, if the laser scanning path is changed, the existing 90° angle scanning method is changed to 60° angle or other angles, so as to obtain a triangular or other shaped multi-level micro-nano composite structure, it can also meet the needs. This embodiment takes the cone-shaped scanning method as an example.
[0021] Furthermore, in order to process a cone-tip anti-reflection structure with a higher aspect ratio, the "V"-shaped scan can also scan several more layers in the z-axis direction and then reduce the width of a surface scan.
[0022] Furthermore, the ultrasonic cleaning time in step three is 0.1h-2h; the deionized water can also be replaced with ethanol or other solutions to remove debris that is not firmly bonded to the surface of the microstructure.
[0023] On the other hand, the present invention also provides a high aspect ratio anti-reflection structure, which is prepared by the above method, and the structure is a cone-shaped micro-nano composite structure.
[0024] Furthermore, the cone-shaped micro-nano composite structure includes a cone-shaped structure layer, an oxide layer and a nanoparticle layer.
[0025] Compared with the prior art, the advantages of the present invention are as follows:
[0026] (1) Compared with the surface coating method, both methods are relatively simple, but the surface structure processed by femtosecond laser has stability that the coating method does not have, will not decompose over time, and is environmentally friendly. The coating method is generally targeted at a specific band, and the surface structure of the present invention is targeted at an ultra-wide spectrum region;
[0027] (2) Compared with the metamaterial method and the traditional laser scanning method, the advantage of the present invention is that it can simply and quickly prepare the required high aspect ratio cone-shaped micro-nano composite structure in the atmospheric environment, and the area of action is ultra-wide spectrum. The metamaterial method has a precisely designed geometric structure and uses the resonant light absorption mechanism to obtain ultra-low surface reflectivity, but the absorption spectrum range strongly depends on the period and size of its constituent structures, is limited to a narrow and specific wavelength range, and the preparation process is complicated; the traditional laser cross-type scanning method cannot well adjust the period and aspect ratio of the micron cone structure, and the achieved wide-spectrum absorption is generally concentrated in the ultraviolet and visible regions, and cannot achieve high absorption in the ultra-wide spectrum range spanning ultraviolet-visible-near infrared-mid-infrared.
[0028] (3) The present invention utilizes the ultrashort pulses and extremely high peak power of femtosecond lasers to ablate and remove materials. The field mirror focused three-dimensional galvanometer processing system can very quickly utilize "V"-shaped scanning to prepare a conical tip micro-nano composite structure with an aspect ratio of 7:1, and can achieve a high absorption rate of more than 98% in the range of 200nm-25μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the "V" type scanning method proposed by the present invention and the traditional cross type scanning method;
[0030] Among them, a is a traditional scanning method, b is a typical electron microscope image of the micro-nano composite structure prepared by the traditional scanning method; c is the "V" type scanning method proposed in the present invention, and d is an electron microscope image of a typical cone tip structure obtained by the "V" type scanning.
[0031] Figure 2 Schematic diagram of the period and depth of the control structure of the traditional scanning method;
[0032] Among them, ab are the schematic diagram and the electron microscope image of the structure when the laser scanning period is large, respectively;
[0033] cd, schematic diagram and electron microscope image of the structure when the laser scanning cycle is slightly smaller;
[0034] ef, are the schematic diagram and electron microscope image of the structure when the laser scanning period and laser spot size match.
[0035] Figure 3 It is a single-step schematic diagram of the "V"-shaped scanning method of the present invention.
[0036] Among them, a is the overall schematic diagram, and bf is the cross-sectional schematic diagram of the scanned and removed area on each layer.
[0037] Figure 4 The electron microscope images of structures of different periods and different depths in the same period prepared on the surface of the copper sample by the present invention are shown.
[0038] Among them, ad is the electron microscope cross-sectional images of different periods, with periods of 20μm, 30μm, 40μm, and 50μm respectively; eh is the cross-sectional image of the cone-tip micro-nano composite structure with a period of 30μm and depths of 120μm, 150μm, 180μm, and 210μm respectively.
[0039] Figure 5 The top view and emissivity test results of the cone-shaped micro-nano composite structure prepared by the present invention. Figures ab are top views of the uniform cone-shaped structure, Figure c is the emissivity test results at different depths with a period of 30μm, and Figure d is the emissivity test result of a sample with a depth-to-width ratio of 7:1, which exceeds 98% in the range of 200nm-25μm, and the emissivity exceeds 99% in the range of 400-700nm.
[0040] Figure 6 It is a cone-shaped micro-nano composite structure processed on other metal materials according to the present invention.
[0041] Among them, ac is the structural electron microscope image and emissivity test result of 314L stainless steel, and df is the structural electron microscope image and emissivity test result of TC4 titanium alloy. DETAILED DESCRIPTION
[0042] The present invention will be further described below in conjunction with the embodiments.
[0043] Example 1
[0044] In this embodiment, a cone-shaped micro-nano composite structure with a depth-to-width ratio of 7:1 is prepared on the copper surface by a "V" scanning method. The specific steps are as follows:
[0045] (1) Processing of samples to be processed;
[0046] First, the copper sample to be processed is placed in a sealed polytetrafluoroethylene beaker with acetone solution and ultrasonically cleaned for 1 hour, then taken out, and then the sample is cleaned with ethanol and deionized water in turn, and a cotton ball dipped in the corresponding solution is grasped with tweezers and wiped in the same direction. During the wiping process, be careful not to leave scratches on the sample surface with the tweezers, and then the sample is placed in a 50℃ low-temperature oven for drying; then the copper sample is taken out for use, and the sample preparation is completed;
[0047] (2) Processing copper samples by femtosecond laser in atmospheric environment;
[0048] First, fix the sample on the two-dimensional mobile platform with traceless glue, adjust the laser power to 300mW, and open the shutter; then adjust the z-axis so that the laser focuses on the upper surface of the sample. Then read the pre-designed processing file into the processing program, and perform direct writing processing by scanning the surface row by row on the x-axis and then scanning the surface column by column on the y-axis. Figure 1 As shown, Figure 1 a is a traditional scanning method, which scans a line on a certain z-axis. The material removal area is wide at the top and narrow at the bottom, and the removal area becomes narrower as it goes deeper into the structure. Figure 1 b is a typical electron microscope image of a micro-nano composite structure prepared by a traditional scanning method. There is a square unablated area on the top of the structure, which seriously affects the overall emissivity of the structure. Moreover, the traditional scanning method cannot well control the period and depth of the structure. Figure 2 a. When the laser scanning period is large, the obtained structure is as follows Figure 2 As shown in b, there is an unablated area on the top of the structure. Figure 2 c. By reducing the scanning period, the unablated area on the top of the structure will also decrease. Figure 2 d. Continue to reduce the scanning cycle, such as Figure 2 e. Only when the laser spot size and scanning cycle of the current processing system match, can the Figure 2 The cone-shaped structure shown in f.
[0049] Figure 1c is the "V" type scanning method proposed by the present invention. In a certain z-axis, the traditional method of scanning a line is changed to scanning a surface, which can realize the removal area of an inverted triangle, and the area can be determined to a certain extent by the processing parameters, so a cone-shaped structure with a high aspect ratio can be realized; Figure 1 d is the electron microscope image of the typical cone tip structure obtained by “V” type scanning. Figure 3 A single-step schematic diagram of the "V" type scanning method of the present invention is given. Figure 3 a is the overall schematic diagram. At this time, the laser is focused on the sample surface and a surface scan is performed. The cross-sectional removal area is as follows: Figure 3 b. Lower the z axis and perform a surface scan with reduced width, the cross section of which is as follows Figure 3 c. Figure 3 d and Figure 3 e Continue to lower the z axis to scan the surface with decreasing width, and repeat this cycle to obtain Figure 3 f and Figure 1 d shows the cone-shaped structure. Figure 4 The electron microscope images of structures of different periods and different depths in the same period prepared on the surface of copper samples by the present invention are given. Figure 4 Figures ad are electron microscope cross-sectional images of different periods, with periods of 20μm, 30μm, 40μm, and 50μm, respectively, which verify that the "V" scan can well adjust the period of the cone tip structure. Figure 4 The cross-sectional diagram of the cone tip micro-nano composite structure with eh period of 30μm and depths of 120μm, 150μm, 180μm and 210μm respectively verifies that the "V" scanning can realize a cone tip micro-nano composite structure with a high aspect ratio. The repetition frequency of the femtosecond laser is 200kHz, the single pulse energy is 40μJ, the laser scanning speed is 200mm / s, the focal length of the field lens is 10cm, the scanning period is 30μm, the number of scans is 10 times, the initial width of the surface scan is 20μm, the width of each layer scan is reduced by 2μm, and the z-axis interlayer spacing is 10μm. Of course, if the laser scanning path is changed, the existing scanning method at an angle of 90° is changed to an angle of 60° or other angles, so as to obtain a multi-level micro-nano composite structure in a triangular shape or other shape, it can also meet the needs. This embodiment takes the cone tip scanning method as an example.
[0050] (3) Ultrasonic removal of copper samples;
[0051] The sample obtained in step 2 was ultrasonically cleaned in deionized water for 1 hour to clean the debris left after processing, leaving only the micro-cones and nano-particle structures that can exist stably, and then dried in a dryer or blown dry with an ear bulb. At this point, the preparation of the high-emissivity copper sample was completed.
[0052] Example 2
[0053] Emissivity test of the prepared cone-shaped micro-nano composite structure.
[0054] The equipment used for the emissivity test is a VERTEX 70 Fourier infrared spectrometer with an integrating sphere and a UV3600 with an integrating sphere. Since the integrating sphere test has requirements on the sample size, a sample with a length and width greater than or equal to 2 cm is quickly prepared by the method described in the present invention for testing. The finally prepared high-emissivity copper sample is placed close to a dedicated integrating sphere, and then the diffuse reflectivity at 200nm-25μm is tested using a Fourier infrared spectrometer and UV 3600, and then the emissivity or absorptivity is obtained according to 1-diffuse reflectivity.
[0055] Depend on Figure 5 It can be observed that the prepared cone-shaped micro-nano composite structure has a uniform morphology. Figure 5 The emissivity test results of the cd show that the high aspect ratio cone-shaped micro-nano composite structure prepared by the "V" scanning method proposed in the present invention has an emissivity that increases with the increase of aspect ratio. Finally, the sample with an aspect ratio of 7:1 can achieve an emissivity of more than 98% in the 200nm-25μm band and an emissivity of more than 99% in the 400-700nm band. The test results of this ultra-wide spectrum high emissivity are at the international leading level.
[0056] Example 3
[0057] In this embodiment, a “V”-shaped scanning method can be used to prepare a high aspect ratio cone-shaped micro-nano composite structure on the surface of 314L stainless steel and TC4 titanium alloy.
[0058] The specific preparation process is the same as in Example 1. Figure 6 The ac gives the test results of the cone-shaped micro-nano composite structure prepared on the surface of 314L stainless steel and its emissivity. Figure 6 The df of gives the cone-shaped micro-nano composite structure prepared on the surface of TC4 titanium alloy and its emissivity test results. Figure 6 , which verifies that the "V"-shaped scanning proposed in the present invention is a universal method for preparing high aspect ratio anti-reflection structures, has no material selectivity, and can be applied to various metal materials and some hard and brittle non-metallic materials.
[0059] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0060] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0061] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a high aspect ratio anti-reflection structure based on laser "V" scanning, characterized in that: The specific steps are as follows: Step 1: Processing of samples to be processed; The metal sample to be processed is placed in a sealed polytetrafluoroethylene beaker with acetone solution, taken out after ultrasonic cleaning, rinsed with ethanol and deionized water in turn, and placed in a low-temperature oven for drying; then the metal sample is taken out for use, and the sample preparation is completed; Step 2: Processing metal samples with femtosecond laser in atmospheric environment; First, the sample is fixed on a two-dimensional mobile platform, which is composed of two one-dimensional mobile translation stages to meet the precise movement of the sample in the XY plane. The femtosecond laser emitted by the femtosecond laser amplifier enters the three-dimensional galvanometer processing system focused by the field lens after beam expansion. The galvanometer of the three-dimensional galvanometer processing system is installed on a z-axis translation stage that can move up and down. The femtosecond laser deflected by the galvanometer is then focused on the upper surface of the sample by the field lens. Then, the pre-designed processing file is read into the processing program, and the "V" scanning method is used for direct writing processing. Finally, the multi-level micro-nano composite structure is prepared on the sample surface by the "V" scanning method of the three-dimensional galvanometer processing system focused by the field lens. Step 3: ultrasonic treatment of metal samples; The sample obtained in step 2 is placed in deionized water for ultrasonic cleaning to clean the debris remaining after processing, leaving only the stable micron cone tip structure and nanoparticle structure, and then dried in a dryer or blown dry with an ear bulb. At this point, the preparation of a metal sample with high emissivity is completed.
2. A method for preparing a high aspect ratio anti-reflection structure based on laser "V" scanning as claimed in claim 1, characterized in that: The sample to be processed in step 1 is copper, aluminum alloy, stainless steel, titanium alloy, silicon carbide, diamond or silicon, etc.; the size of the metal sample is 3cm-10cm, the thickness is 1mm-10mm, the ultrasonic time is 0.1h-2h, and the low-temperature oven temperature is set to 50℃-100℃.
3. A method for preparing a high aspect ratio anti-reflection structure based on laser "V" scanning as claimed in claim 1, characterized in that: The x-axis and y-axis moving ranges of the two-dimensional moving platform in step 2 are 0-10cm, and the moving range of the z-axis translation stage is 0-10cm with an accuracy of 1μm. The galvanometer used in the three-dimensional galvanometer processing system is composed of an XY optical scanning head, an electronic drive amplifier and an optical reflective lens. The signal provided by the computer controller is sent to the electronic drive amplifier, which is used to drive the XY optical scanning head to control the high-speed deflection of the laser beam in the XY plane with a moving accuracy of 10-100nm. The laser polarized by the galvanometer is then focused on the sample surface through the field lens to realize femtosecond laser direct writing processing.
4. A method for preparing a high aspect ratio anti-reflection structure based on laser "V" scanning as claimed in claim 1, characterized in that: The fundamental wavelength of the femtosecond laser in step 2 is 1030nm, which becomes 515nm after double frequency, which is a visible region femtosecond laser, or a 343nm near-ultraviolet femtosecond laser obtained by triple frequency; the repetition frequency of the laser is 50kHz-1000kHz, and the pulse width is 280fs; the focal length of the focusing field lens used is 5-20cm; the single pulse energy of laser ablation is 1-100μJ, the laser scanning speed is 1-1000mm / s, the point spacing of the processing data is 50-10000nm, the period is 10-100μm, the width of the surface scanning is 10-100μm, and the layer spacing is 1-30μm.
5. The method for preparing a high aspect ratio anti-reflection structure based on laser "V" scanning as claimed in claim 1, characterized in that: In step 2, a "V" scanning method is used for direct writing processing, which specifically includes the following contents: First, a surface scan with a certain width is performed from left to right and then from right to left on the x-axis, wherein the certain width is less than one cycle; then, a surface scan is performed after an interval of one cycle, and the scanning is repeated in this way, and the number of back-and-forth surface scans on the x-axis is equal to the total width of the sample to be processed divided by the cycle in the y-direction; similarly, after the x-axis scan is completed, the y-axis scan is performed back and forth, thus realizing the surface scan at the same z-axis position; next, a second scan is performed, the z-axis position is lowered, so that the laser focus further penetrates into the structure, the width of the surface scan is reduced, and the cyclic surface scans of the x-axis and y-axis are repeated; the z-axis is continued to be lowered to perform a surface scan with a reduced width, and this cycle is repeated until the surface scan width is reduced to 0, thereby realizing the processing of the set high aspect ratio structure.
6. A method for preparing a high aspect ratio anti-reflection structure based on laser "V" scanning as claimed in claim 1, characterized in that: The ultrasonic cleaning time in step three is 0.1h-2h; the deionized water can also be replaced with ethanol or other solutions to remove debris that is not firmly bonded to the surface of the microstructure.
7. A method for preparing a high aspect ratio anti-reflection structure based on laser "V" scanning as claimed in claim 1, characterized in that: The ultrasonic cleaning time in step 3 is 0.1h-2h.
8. A high aspect ratio anti-reflection structure, characterized in that: The structure is prepared by the method described in any one of claims 1 to 7, and is a micro-nano composite structure with a cone tip.
9. The high aspect ratio anti-reflection structure according to claim 8, characterized in that: The cone-shaped micro-nano composite structure comprises a cone-shaped structure layer, an oxide layer and a nano-particle layer.
Citation Information
Patent Citations
Rotating table type femtosecond laser direct writing method and device
CN104959730A
Femtosecond laser scanning power regulation device and method and femtosecond laser processing system
CN104979748A
Aluminum alloy surface with high-emissivity multistage micro-nano composite structure and preparation method of aluminum alloy surface
CN115787026A
Method for reducing total loss of three-dimensional optical waveguide by femtosecond laser variable-speed scanning and application
CN118143428A
Femtosecond laser preparation method of micro-nano cavity array structure and anti-reflection metal plate prepared by adopting method
CN118371881A